Soviet documents on Nazi atrocities, illustrated by some 200 original photographs (London New York Melbourne : Hutchinson & Co.)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; oorlogsmisdaden; Sovjet-Unie.